2009
DOI: 10.1007/s10750-009-9830-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific attenuation coefficients of optically active substances and their contribution to the underwater ultraviolet and visible light climate in shallow lakes and ponds

Abstract: Sunlight penetration through the water column is controlled by the amount and kind of materials dissolved and suspended in the water. Understanding UV penetration in its complexity is essential for the prediction of the impact of UV radiation on aquatic ecosystems. However, only limited data are available on the penetration of UVR into shallow waters rich in inorganic suspended solids and chromophoric dissolved organic matter (CDOM). The same is true for the specific attenuation coefficients of light-absorbing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…Photosynthetically active radiation (PAR, 400-700 nm) was considered to be 47% of global radiation (Wetzel and Likens 2000). Underwater light intensity was calculated for each mm of the water column using the vertical light attenuation coefficient determined by the empirical formula of V.- Balogh et al (2009) on the basis of the chlorophyll a concentration, total suspended solids and Pt colour. Light attenuation of the ice cover was also taken into account.…”
Section: Photosynthesis Measurementmentioning
confidence: 99%
“…Photosynthetically active radiation (PAR, 400-700 nm) was considered to be 47% of global radiation (Wetzel and Likens 2000). Underwater light intensity was calculated for each mm of the water column using the vertical light attenuation coefficient determined by the empirical formula of V.- Balogh et al (2009) on the basis of the chlorophyll a concentration, total suspended solids and Pt colour. Light attenuation of the ice cover was also taken into account.…”
Section: Photosynthesis Measurementmentioning
confidence: 99%
“…Moreover, it significantly reduces harmful effects of UV radiation on aquatic organisms (Zhang et al, 2011b). Several studies in temperate aquatic systems have demonstrated the role of CDOM in the light attenuation (Christian and Sheng, 2003;Balogh et al, 2009;Yamaguchi et al, 2013), but the effect of CDOM in tropical systems still requires effort (Obrador and Pretus, 2008) Optical properties in tropical systems duction, which is responsible for the regeneration of nutrients in the water (Lønborg et al, 2010). It also operates in the physical, chemical and biological processes of transport and availability of nutrients and the development of blooms of phytoplankton in eutrophic lakes (Qualls and Richardson, 2003;Coble, 2007;Stedmon et al, 2007) and it is an important component to estimates and effective management of water quality and eutrophication control (Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…In the case 66 of UVR, recent studies have demonstrated that simple laboratory measurements allow for establishing 67 reliable relationships between concentrations of optically active substances (such as chlorophyll, 68 dissolved organic matter and total suspended solids) and the underwater UVR light climate in natural 69 systems [10]. 70 71 These approaches are based on the theoretical assumption that light passing through a dilute 72 suspension of cells should obey Beer-Lambert's law [10].…”
Section: Integrative Approaches For Par Modelling and Uvr Extinction mentioning
confidence: 99%
“…This assured a 139 homogeneous light pathway for UVR from the surface of the liquid to the sensor in the bottom of the 140 beaker for each sample. This method had been previously applied successfully to measure irradiance 141 extinction in a volume of water that was too shallow to use a radiometer [10] and measuring systems were tested (Tab. 1).…”
Section: Integrative Approaches For Par Modelling and Uvr Extinction mentioning
confidence: 99%
See 1 more Smart Citation